Factors influencing abortion care-seeking outside of formal healthcare settings: lived experiences from Rwandan young women - Jean Pierre Ndayisenga; Assumpta Yamuragiye; Abe Oudshoorn; Godfrey Katende; Aimable Nkurunziza; Olive Tengera; Jean Bosco Henri Hitayezu; Justine Bagirisano; Jeanne d' Arc Ayinkamiye; Gilbert Uwitonze (BMC, 2024)
Abstract Background Informal abortions, commonly known as unsafe abortions, refer to all induced abortions that occur outside of formal healthcare settings conducted without the assistance of a licensed, trained healthcare provider. Despite the legalization of safe induced abortion care services, informal abortions continue to be among the major causes of maternal mortality and morbidity among young women in Rwanda living in rural areas with limited or no access to safe abortion care services. The purpose of this qualitative study was to gain an in-depth understanding of the lived experience of seeking informal abortions from the perspective of young women in rural Rwanda and to identify the underlying factors for these women seeking abortion care services outside of the formal healthcare setting. Methods This qualitative study was guided by a descriptive phenomenology in rural Rwanda, specifically in a selected district located in the Northern Province of Rwanda. Ten young women between 18 and 24 years of age, who had the experience of seeking informal abortion services from informal providers within the last eight years participated in audio-recorded, in-depth, face-to-face interviews. Collected data were analyzed using Colaizzi's (1978) seven steps of the phenomenological method. Results The study found that young Rwandan women still seek unregulated abortions to end their unintended pregnancies due to limited access to or utilization of sexual reproductive health and rights services. Among the reasons for seeking abortion care services outside of the formal healthcare setting in Rwanda were sociocultural and economic factors and the stigma associated with terminating unintended pregnancies before marriage. Conclusion In light of the findings of this study, the authors recommend the Ministry of Health and its stakeholders to expand access to comprehensive adolescent and youth-friendly reproductive health and reproductive rights while addressing the sociocultural stigma through public awareness and economic factors that play a big role in unregulated abortions rather than safe abortion care services.